Τhe Antioxidant Function of HDL in Atherosclerosis. (February 2020) - Xepapadaki, Eva; Zvintzou, Evangelia; Kalogeropoulou, Christina; Filou, Serafoula; Kypreos, Kyriakos E.
Atherosclerosis is a multistep process that progresses over a long period of time and displays a broad range of severity. In its final form, it manifests as a lesion of the intimal layer of the arterial wall. There is strong evidence supporting that oxidative stress contributes to coronary heart disease morbidity and mortality and antioxidant high-density lipoprotein (HDL) could have a beneficial role in the prevention and prognosis of the disease. Indeed, certain subspecies of HDL may act as natural antioxidants preventing oxidation of lipids on low-density lipoprotein (LDL) and biological membranes. The antioxidant function may be attributed to inhibition of synthesis or neutralization of free radicals and reactive oxygen species by HDL lipids and associated enzymes or transfer of oxidation prone lipids from LDL and biological membranes to HDL for catabolism. A limited number of clinical trials suggest that the increased antioxidant potential of HDL correlates with decreased risk for atherosclerosis. Some nutritional interventions to increase HDL antioxidant activity have been proposed with limited success so far. The limitations in measuring and understanding HDL antioxidant function in vivo are also discussed.